2018
DOI: 10.3988/jcn.2018.14.4.530
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictors of Excessive Daytime Sleepiness in Patients with Parkinson's Disease

Abstract: Background and PurposeExcessive daytime sleepiness (EDS) is a common complaint among patients with Parkinson's disease (PD). Several factors have been associated with EDS in PD, especially neuropsychiatric symptoms. This study aimed to determine the relationships between neuropsychiatric symptoms, sociodemographic and clinical parameters, and EDS in PD.MethodsThis cross-sectional study analyzed 85 patients with PD. All patients underwent socioeconomic and clinical data evaluations followed by a psychiatric int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Factors associated with formal ID diagnosis in PD have received little attention. Nevertheless, similar to the general population, age, female gender, medical comorbidities, poor quality of life, anxiety, symptoms of depression, fatigue, and daytime sleepiness have been associated with insomnia complaint severity in PD (Chung et al, ; Gjerstad, Wentzel‐Larsen, Aarsland, & Larsen, ; Junho, Kummer, Cardoso, Teixeira, & Rocha, ; Kurtis, Rodriguez‐Blazquez, & Martinez‐Martin, ; Ratti et al, ; Tholfsen, Larsen, Schulz, Tysnes, & Gjerstad, ; Zoccolella et al, ). In contrast, clinical features of the disease (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Factors associated with formal ID diagnosis in PD have received little attention. Nevertheless, similar to the general population, age, female gender, medical comorbidities, poor quality of life, anxiety, symptoms of depression, fatigue, and daytime sleepiness have been associated with insomnia complaint severity in PD (Chung et al, ; Gjerstad, Wentzel‐Larsen, Aarsland, & Larsen, ; Junho, Kummer, Cardoso, Teixeira, & Rocha, ; Kurtis, Rodriguez‐Blazquez, & Martinez‐Martin, ; Ratti et al, ; Tholfsen, Larsen, Schulz, Tysnes, & Gjerstad, ; Zoccolella et al, ). In contrast, clinical features of the disease (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recent polysomnography studies by Lee et al have found an association between depression and insomnia [24], and an association between depression and restless legs syndrome has also been found in other studies [25][26][27]. Depression has been shown to be a risk factor for excessive daytime sleepiness [28,29]. Christopher et al demonstrated that nightmares were significantly associated with depressive symptoms [30], although this needs to be confirmed using polysomnography.…”
Section: Discussionmentioning
confidence: 93%
“…EDS was known as one of the most frequent sleep disorders in PD. Usually, male gender, older age, nighttime sleep problems, and dopaminergic agonist usage were related to increased risk of EDS in PD (26,27). However, there were other studies indicating that apart from dopaminergic agonist, larger levodopa dosage was more significantly associated with EDS (26,28,29).…”
Section: Discussionmentioning
confidence: 98%